(untitled) (Physical Education, Health and Social Sciences, 2025)
Laser induced breakdown spectroscopy (LIBS) is a non-destructive optical emission analysis technique employed in this study to investigate the elemental composition of tobacco cigarette brands available in local markets in Pakistan. Utilizing a 1064 nm Nd: YAG laser, we generated plasma emission from tobacco pellet targets. The analysis of the optical emission spectra revealed the presence of several elements, including Calcium (Ca), Sodium (Na), Magnesium (Mg), Barium (Ba), Lead (Pb), Lithium (Li), and Hydrogen (H) each identified by their relative abundances. To assess the electron temperature along the plasma plume’s propagation, we applied the Boltzmann plot method to the calcium atomic transition lines, revealing an electron temperature near the target of approximately 16610 K. The study also noted a spatial variation in electron temperature, which decreased from 16610 K to 5720 K as the distance from the target surface increased, indicating a consistent trend of declining electron temperature with distance. Additionally, we analyzed the Stark broadening profile of the singly ionized calcium emission line at 393.36 nm to estimate the electron number density (Ne) near the target, which was measured at 5.4×1016 cm-3.